Anisotropic Growth of Porous Anodic Alumina and Its Potential Application in Three-Dimensional Nanostructure Construction. (4th May 2011) - Dai, Jinhui; Shi, Leiyan; Tian, Jintao; Zhu, Zhibin; Huang, Xiang; Wu, Pingwei; Qu, Xiaofei
Abstract : The porous anodic alumina was fabricated by means of electrochemical oxidation using Al foil as a substrate in oxalic acid under constant anodic voltage at room temperature. Prior to anodization, the substrate surface with roughness in microscale was obtained through electrochemical treatment. The tube growth on the substrate was investigated using a scanning electron microscope (SEM). The results showed that the tube growth behavior of the porous anodic alumina was strongly dependent on the surface roughness. In presence of sphere-shaped cavities in microscale (diameter of 5 30 μ m) on the surface of the substrate, the nanotubes were growing essentially away from the center of curvature of each cavity, forming individual growing regions separated by visible interface. The tube branching and tube cutoff were evidently observed in the growing regions and along the interface, respectively. Anisotropic growth of porous anodic alumina suggested its potential application in three-dimensional nanostructure construction.